Eksistensi Jajanan Lumpia Sebagai Kuliner Khas Di Kawasan Wisata Pantai Sanur - suarmana, I Wayan Restu (Jurnal Kajian Pariwisata Dan Perhotelan, 2024)
Sanur is a very beautiful beach tourist area in the city of Denpasar. Apart from the beautiful panoramic views of the beach, Sanur is also famous for its spring roll snacks. This snack is a culinary specialty when visiting Sanur Beach. As time goes by, the existence of spring roll snacks, especially on Sanur Beach, is increasingly being rivaled by modern snacks. Previously, spring rolls were very popular, but with the existence of this modern snack, spring rolls are now rarely popular except on weekends. The data collection techniques used in this research were observation, in-depth interviews and literature study. Observations were carried out at Sanur Beach (Segara Beach, Sindu Beach, Karang Beach, and Mertasari Beach). Interviews were carried out using snowball sampling. Literature study in the form of previous research that is still relevant to this research, theoretical basis and concepts obtained from books, journals and articles that are still relevant to this research. The existence of spring roll snacks is currently experiencing a decline in interest, this is due to the large number of traders selling modern snacks and other traditional foods on Sanur Beach. The modern snacks such as burgers, fries, kebabs, hot dogs and other types of modern food. Currently, spring roll traders mostly sell outside Sanur Beach, they only sell on weekends, on other days they sell in the Puputan field, Renon field and even sell around to people's homes.